The technology of formation of teamwork skills in terms of project-based learning students - Svetlana D. Lipatova; Evgeniya A. Khokholeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Each era has its own requirements for the level of competence formation of employees. The fourth industrial revolution focuses on the development of human potential. One of the forms that allow us to reveal the potential capabilities of the individual is project activity.